2014
DOI: 10.1016/s1474-4422(14)70142-5
|View full text |Cite
|
Sign up to set email alerts
|

Oral cysteamine bitartrate and N-acetylcysteine for patients with infantile neuronal ceroid lipofuscinosis: a pilot study

Abstract: Summary Background Infantile neuronal ceroid lipofuscinosis (INCL) is a devastating neurodegenerative lysosomal storage disease caused by mutations in the CLN1 gene encoding palmitoyl-protein thioesterase-1 (PPT1). PPT1-deficiency causes lysosomal ceroid accumulation leading to INCL pathogenesis. Previously, we reported that phosphocysteamine and N-acetylcysteine mediated ceroid depletion in cultured cells from INCL patients. We conducted a pilot study to determine whether a combination of cysteamine bitartra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 47 publications
3
55
0
Order By: Relevance
“…We have demonstrated that, among the regions that we measured separately, atrophy begins earliest and proceeds fastest in the cerebrum, with the thalamus lagging slightly behind; there is later involvement of the cerebellum and then the brainstem. Although our patients had a variety of different gene mutations, the pattern and rate of atrophy that we observed did not appear to vary by genotype, in agreement with previous reports that these particular gene mutations are clinically indistinguishable 16, 19 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We have demonstrated that, among the regions that we measured separately, atrophy begins earliest and proceeds fastest in the cerebrum, with the thalamus lagging slightly behind; there is later involvement of the cerebellum and then the brainstem. Although our patients had a variety of different gene mutations, the pattern and rate of atrophy that we observed did not appear to vary by genotype, in agreement with previous reports that these particular gene mutations are clinically indistinguishable 16, 19 .…”
Section: Discussionsupporting
confidence: 92%
“…We would have liked to have compared our quantitative atrophy measurements to previous reports on the natural history of volume loss in INCL 16, 25 to evaluate the treatment benefits of cysteamine bitartrate and N-acetylcysteine; in particular we would have liked to determine whether the treatment resulted in any delay in atrophy onset or any slowing of the rate of atrophy. However, since all previous studies evaluating atrophy in INCL used qualitative scoring without correspondence to any particular absolute or fractional volume loss, we could not determine the effect of the treatment on brain atrophy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Decrease in the number and size of GRODs was observed after the first posttreatment follow-up and in the subsequent follow-up GROD levels were undetectable indicating that the treatment had beneficial effects in patients. 5 …”
Section: Small Molecule Therapeutics Evaluated In Cln3 Disease (Jncl)mentioning
confidence: 99%